THE IMPORTANCE OF DIGITAL LITERACY AND HOW TO DEVELOP IT IN PRIMARY SCHOOLS (Conferencea, 2022)
The significance of digital literacy for pupils is becoming increasingly clear as technology continues to permeate both children's and adults' everyday lives. The capacity to use technology efficiently has become crucial for modern success in everything from social relations to entertainment to education. New teaching and learning methods in the classroom are also made possible by digital literacy. Students are learning new techniques for interacting with their interests through the internet and other digital media. When it comes to reading or discovering more about potential interests, they are no longer limited to only physical text. This scientific article will analyze what “digital literacy ” means, and how to develop digital literacy and make it common among pupils. To achieve this, teachers should have actual knowledge and methodology about digital literacy.